A new type of anti-phase boundaries in the T(Al20Cu2Mn3) phase and the pre-deformation effect on T phase precipitation. (December 2020) - Chen, Y.Q.; Tang, Z.H.; Pan, S.P.; Liu, W.H.; Song, Y.F.; Liu, Y.; Zhu, B.W.; Zhou, W.; Shen, F.H.
Abstract: The anti-phase boundaries (APBs) in the T (Al20 Cu2 Mn3 ) phase and the interfaces of the T phase with an Al matrix were observed. The effects of pre-deformation on the precipitation behavior of T phase and hardening behavior of alloy were investigated by hardness measurement, mechanical tensile test, transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HRTEM). Results show that two kinds of APBs exist in the T phase, i.e . 101T and 301T -type APBs. The first is commonly observed, while the latter is newly found and only coexists with the first to form a zig-zag shaped APB. Whatever its orientation relationships (ORs) with Al matrix and cross-section (CS) shape, the T phase always retains its interfaces constituted by 200T, 101T and 301T planes. Pre-deformation increases the APBs in T phase and intensifies the irregularity of the CS shape of a T phase. Besides, it also promotes the nucleation and refines the size of the T phase during precipitation which enhances the mechanical properties of the alloy. Highlights: A new type of APB with slip displacement of 1/4 <301>T is found in the T-phase. The 301T type APB coexists with 101T type APB to form a zig-zag-shaped APB. The T-phase interfaces are always constituted by 200T, 101T, and 301T planes. Pre-deformation increases APBs and causes a more irregular cross-section of T-phase. Pre-deformation promotes the nucleation rate and refines T-phase.